Prediction of transplant outcome after 24‐hour ex vivo lung perfusion using the Organ Care System in a porcine lung transplantation model. Issue 2 (12th September 2018) - Sommer, Wiebke; Salman, Jawad; Avsar, Murat; Hoeffler, Klaus; Jansson, Katharina; Siemeni, Thierry N.; Knoefel, Ann‐Kathrin; Ahrens, Linda; Poyanmehr, Reza; Tudorache, Igor; Braubach, Peter; Jonigk, Danny; et al.
Abstract : Ex vivo lung perfusion (EVLP) has become routine practice in lung transplantation. Still, running periods exceeding 12 hours have not been undertaken clinically to date, and it remains unclear how the perfusion solution for extended running periods should be composed and which parameters may predict outcomes. Twenty‐four porcine lungs underwent EVLP for 24 hours using the Organ Care System (OCS). Lungs were ventilated and perfused with STEEN's solution enriched with erythrocytes (n = 8), acellular STEEN's solution (n = 8), or low‐potassium dextran (LPD) solution enriched with erythrocytes (n = 8). After 24 hours, the left lungs were transplanted into recipient pigs. After clamping of the contralateral lung, the recipients were observed for 6 hours. The most favorable outcome was observed in organs utilizing STEEN solution enriched with erythrocytes as perfusate, whereas the least favorable outcome was seen with LPD solution enriched with erythrocytes for perfusion. Animals surviving the observation period showed lower peak airway pressure (PAWP) and pulmonary vascular resistance (PVR) during OCS preservation. The results suggest that transplantation of lungs following 24 hours of EVLP is feasible but dependent on the composition of the perfusate. PAWP and PVR during EVLP are early and late predictors of transplant outcome, respectively. Abstract : Long‐term ex vivo lung perfusion using a buffered extracellular solution enriched with erythrocytes as perfusate leads to excellent preservation outcomes and peak airway pressure in a porcine model.